Training the Modern Manager in the Context of the Competence Approach - S.V., Dmitrichenkova (2020)
The difficulties which the Russian Federation is facing in the social and economic spheres are connected with its integration into the world context, strengthened positions of the market economy, the perfection of the system of secondary and higher professional education, the innovative approach to training pedagogical specialists. Besides, the situation in the country facilitates the perception of managerial education as a constituent of global personal learning in the conditions of professional education whose main backbone is the manager able to meet the requirements of the new economic reality. Some experts forecast a specific “managerial revolution”, which, as they say, will occur in the nearest future and become one of the reasons for our country to overcome the economic stagnation. It is suggested that “the human factor” and raising the qualification of managers will become key directions of Russia’s social and economic development. Nowadays, providing the labor sector with managers of the new type, i.e. mobile, economically-minded, able to achieve good results in their profession due to the advanced level of their innovative entrepreneurial competence (IEC), is a complex task which is facing the secondary and higher professional education. In order to solve it, the government pays special attention to training specialists in the field of management, which is implied by official requirements to the content of the educational process presented in the most important federal documents: The Law About Education in the Russian Federation; The National Doctrine of Russian Education Development (till 2025) and others.